Kepemimpinan Transformasional Kepala Sekolah Dalam Memperkuat Kompetensi Pedagogik Guru: Studi Kasus Di Sdn Sinarsari Dan Sdn Neglasari, Kecamatan Ciranjang, Indonesia - Resna Yuanda Syarip; Ayi Najmul Hidayat; Sobari Sobari (Journal of Innovative and Creativity, 2026)
This study explores the role of transformational leadership in strengthening the pedagogical competence of elementary school teachers within the context of Indonesia’s Merdeka Curriculum implementation. Employing a qualitative case study design, the research was conducted at two public elementary schools, namely SDN Sinarsari and SDN Neglasari, located in Ciranjang District, Cianjur Regency. Data were collected through semi-structured interviews, non-participant observations, and document analysis, involving 12 participants consisting of school principals, teachers, and educational staff. The findings reveal three main themes: (1) exemplary leadership that inspires teachers through professional role modeling, (2) humanistic academic supervision that emphasizes dialogic coaching rather than inspection, and (3) collaborative empowerment through school-based professional development. These transformational leadership practices were found to contribute significantly to improvements in lesson planning quality, classroom instructional strategies, and teachers’ professional confidence. The study concludes that transformational leadership, when grounded in relational and context-sensitive approaches, can function as an effective catalyst for pedagogical improvement, particularly in schools facing limited resources. The findings reinforce theoretical perspectives on localized leadership models and offer practical guidance for school principals and policymakers in efforts to enhance instructional quality. Future research is recommended to examine the long-term impact and scalability of transformational leadership practices across diverse educational contexts.